Business the Sony way : - Luh, Shu Shin (Capstone, 2003)
This book tells the story of Sony's past and present, and the vision and drive of founders, Masaru Ibuka and Akio Morita. Beyond narrative history, the book serves as a case study for how entrepreneurs, with the right combination of tenacity, passion, creativity and an eye for the future, can build a company from the humblest of beginnings into a global giant, with operating revenues of more than US